The crucial role of fecal management systems in intensive care - Gutting, Tobias; Pfützner, Andreas (Expert review of medical devices, 2024)
Patients in intensive care units (ICUs) frequently lose control over their fecal continence leading to fecal incontinence (FI). We provide an overview of existing medical devices, which are supposed to alleviate FI-related problems. Fecal management systems (FMS) prevent infections and complications. They reduce the risk of pressure ulcers and fecal incontinence. The systems enhance patient comfort and mitigate emotional distress during illness. Furthermore, FMS facilitate nursing care by reducing the incontinence-related workload. Finally, these systems can help minimize treatment costs by preventing complications, and reduction of extended hospital stays and additional treatments. Several well accepted systems made of silicone are on the market. A polyurethane-based soft balloon FMS (hygh-tec® basic-plus) has also been introduced, offering more comfort to the patient, safer handling for the healthcare professionals, and provides reliable leakproof access to the patient’s colon. In addition to contamination-free fecal diversion, the trans-anal sealing mechanism of the device also allows for irrigation and delivery of medication into the colon. FMS in ICUs are integral to patient care and dignity. Recognizing and prioritizing the importance of these systems is essential for providing the highest standard of care to critically ill patients in the ICU.
Gesehen am 28.11.2024